ANIMAL MOTIFS ON PREHISTORIC POTTERY IN MESOPOTAMIA - Jaber, Ali Abdul Hussein (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to explore the symbolic and artistic significance of animal motifs depicted by ancient humans, focusing on their application to pottery and their lasting influence on subsequent artistic traditions. Method: A qualitative analysis was conducted by examining various animal motifs painted on ancient pottery vessels, complemented by a historical review of their cultural and functional contexts. The study analyzed the use of natural pigments and artistic techniques employed despite the limited tools available during the period. Results: The findings reveal that animal motifs served multiple purposes, including protection from perceived dangers, magical practices in hunting, and artistic expression. These motifs, characterized by their symbolic nature and precise execution, illustrate the aesthetic sensibilities of ancient Iraqi artists. Their enduring presence influenced artistic developments in later eras, indicating a continuity of symbolic representation in Mesopotamian art. Novelty: This research highlights the early integration of symbolic motifs in utilitarian objects, demonstrating how primitive artistic practices contributed to the evolution of cultural and artistic identities in ancient Iraq, an aspect often underrepresented in existing archaeological studies.